Emotional labor of nurses in the front line against the COVID-19 pandemic - Paula Manuela Jorge Diogo; Maria Odete Carvalho Lemos e Sousa; Joana Rita Guarda da Venda Rodrigues; Tânia Alexandra de Almeida Martins de Almeida e Silva; Márcia Leandra Ferreira Santos (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze nurses' experiences in the front line of the fight against the COVID-19 pandemic regarding the performance of emotional labor (EL), aiming at its characterization and identification of support strategies and development opportunities of nurses and practices. Methods: Qualitative, descriptive, and exploratory study, with content analysis of eleven written narratives and reports from a focus group composed of nurses with experience in caring for patients with COVID-19 from different Hospital Centers in Lisbon, Portugal. Results: Five themes were extracted: 1) Challenges experienced by nurses in the frontline; 2) Emotions experienced by nurses in service care; 3) Emotional responses of nurses and patients: impact on care; 4) EL of nurses in the patient care process; 5) Opportunities for development in the face of the emotional challenge required of nurses in combating COVID-19. Final considerations: The nurses demonstrated the ability to transform this profoundly emotional experience positively.